Phraseologies In German Related To Animal Wildlife - Abdiloyev, Sh.O. (PT. Batari Edu Calya, 2023)
German and Uzbek. The focus is on badger, lynx, frog, bear, rabbit, donkey, and pig, bringing a special dimension to the way these two languages represent the relationship between humans and nature. Comparative analysis methods are used to investigate differences and similarities in linguistic structures and cultural contexts, providing an in-depth understanding of how German and Uzbek peoples articulate their values, beliefs, and experiences through this unique phraseology. This research approach includes representative sample selection, linguistic and semantic analysis, and contextual comparison. By understanding the way zoomorphemism phraseology reflects worldview and culture, this research seeks to unravel the linguistic richness and cultural values embedded in language. The results can provide significant insights into the uniqueness and continuity of these linguistic and cultural aspects, enriching our understanding of linguistic heritage in the context of multicultural societies.